2015
DOI: 10.1038/cdd.2015.3
|View full text |Cite|
|
Sign up to set email alerts
|

The role of CD95 and CD95 ligand in cancer

Abstract: CD95 (Fas/APO-1) and its ligand, CD95L, have long been viewed as a death receptor/death ligand system that mediates apoptosis induction to maintain immune homeostasis. In addition, these molecules are important in the immune elimination of virus-infected cells and cancer cells. CD95L was, therefore, considered to be useful for cancer therapy. However, major side effects have precluded its systemic use. During the last 10 years, it has been recognized that CD95 and CD95L have multiple cancer-relevant nonapoptot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
224
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(260 citation statements)
references
References 174 publications
11
224
1
1
Order By: Relevance
“…However, normal somatic cells also express Fas receptor. For example, hepatocytes are highly sensitive to FAS-mediated apoptosis; the systemic injection of high-dose Jo2 antibody induces apoptosis in the liver (28). Thus, FAS-activating antibody needs to be specifically delivered to tumor cells to avoid liver damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, normal somatic cells also express Fas receptor. For example, hepatocytes are highly sensitive to FAS-mediated apoptosis; the systemic injection of high-dose Jo2 antibody induces apoptosis in the liver (28). Thus, FAS-activating antibody needs to be specifically delivered to tumor cells to avoid liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…4A). As reported before, binding of Fas ligand or Fas-activating antibodies to Fas receptor triggers apoptosis through cell-intrinsic pathway (28). We tested whether a Fas-activating antibody can induce Fas-mediated cell death in Kras −/− cells.…”
Section: Transcriptome Analysis Of Kras Knockout Cells Revealed Distimentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies, on failed apoptosis, TRAILR signaling was reported to lead Capasee-dependent cleavage of RHO-associated protein kinase 1 (ROCK1), activating RHO GTPase and causing membrane blebbing and cell migration (Somasekharan et al 2013). Moreover, various non-apoptotic, pro-oncogenic functions were described in FAS signaling, including stimulation of proliferation and migration (Peter et al 2015). However, not only proproliferatives effects, FAS signaling can also exert pro-survival functions.…”
Section: Apoptosismentioning
confidence: 99%